Identifying Pronunciation Errors among Iraqi EFL University learners - Hayder AbdulHasan Hamza; Noora Adnan Tawfeeq; Fatimah Jammal Al-Quraishi (مجلة الباحث, 2025)
A test is an essential device for teachers as it helps to evaluate the performance of their students in English language, and for learners because it assists them to discover the weakness and strength areas of their performances. Teachers want to measure different language skills of their students like pronunciation tests that have showed their ability in, like spelling listening and comprehension. The test is a set of words (about 20 words) reads to the students once only by the teacher .The students' task is to read them carefully in normal speed, while the researchers record the voice of each student when he reads. The present study aims to identify errors of learners at the university stage in pronunciation